Mucosal Infections and Invasive Potential of Nonencapsulated Streptococcus pneumoniae Are Enhanced by Oligopeptide Binding Proteins AliC and AliD - Jessica L. Bradshaw (American Society for Microbiology, 2018)
ABSTRACT Nonencapsulated Streptococcus pneumoniae (NESp) is an emerging human pathogen that colonizes the nasopharynx and is associated with noninvasive diseases such as otitis media (OM), conjunctivitis, and nonbacteremic pneumonia. Since capsule expression was previously thought to be necessary for establishment of invasive pneumococcal disease (IPD), serotype-specific polysaccharide capsules are targeted by currently licensed pneumococcal vaccines. Yet, NESp expressing oligopeptide binding proteins AliC and AliD have been isolated during IPD. Thus, we hypothesize AliC and AliD are major NESp virulence determinants that facilitate persistence and development of IPD. Our study reveals that NESp expressing AliC and AliD have intensified virulence compared to isogenic mutants. Specifically, we demonstrate AliC and AliD enhance murine nasopharyngeal colonization and pulmonary infection and are required for OM in a chinchilla model. Furthermore, AliC and AliD increase pneumococcal survival in chinchilla whole blood and aid in resistance to killing by human leukocytes. Comparative proteome analysis revealed significant alterations in protein levels when AliC and AliD were absent. Virulence-associated proteins, including a pneumococcal surface protein C variant (CbpAC), were significantly downregulated, while starvation response indicators were upregulated in the double mutant relative to wild-type levels. We also reveal that differentially expressed CbpAC was essential for NESp adherence to epithelial cells, virulence during OM, reduction of C3b deposition on the NESp surface, and binding to nonspecific IgA. Altogether, the rise in NESp prevalence urges the need to understand how NESp establishes disease and persists in a host. This study highlights the roles of AliC, AliD, and CbpAC in the pathogenesis of NESp. IMPORTANCE Despite the effective, widespread use of licensed pneumococcal vaccines over many decades, pneumococcal infections remain a worldwide burden resulting in high morbidity and mortality. NESp subpopulations are rapidly rising in the wake of capsule-targeted vaccine strategies, yet there is very little knowledge on NESp pathogenic potential and virulence mechanisms. Although NESp lacks a protective capsule, NESp lineages expressing AliC and AliD have been associated with systemic infections. Furthermore, higher antibiotic resistance rates and transformation efficiencies associated with emerging NESp threaten treatment strategies needed to control pneumococcal infections and transmission. Elucidating how NESp survives within a host and establishes disease is necessary for development of broadened pneumococcal prevention methods. Our study identifies virulence determinants and host survival mechanisms employed by NESp with a high pathogenic potential. Moreover, our study also identifies virulence determinants shared by NESp and encapsulated strains that may serve as broad prevention and therapeutic targets.